JENIS TUMBUHAN BERKHASIAT OBAT DI KAWASAN TEMBAWANG OMPU OBU DUSUN JAMBU - Sabinus Beni (Bapelitbang Kabupaten Batang, 2022)
Indonesia is a country rich in flora and fauna, the relationship with forest flora in Indonesia is found in many types of medicinal plants from various habits and families. The purpose of this study was to determine the types of medicinal plants found in the Tembawang Ompu Obu Hamlet area. Jambu, Jangkang District, Sanggau Regency and to find out the benefits of medicinal plants by the local community. This study used a field survey (observation) method, interviews and literature studies. The results showed that the Tembawang Ompu Obu Forest in Jambu Hamlet contained 48 types of medicinal plants divided into 33 families that were used by the local community to treat more than 20 types of diseases. Meanwhile, based on the grouping of shrubs, there are 13 species, 12 species of trees, 8 species of herbs, and then 6 species of lianas.